Kinetic and physiological responses of Listeria monocytogenes to novel non-thermal inactivation treatments and their application to minimally processed seafood - Bittencourt, CR (2009)
Listeria monocyto genes is a facultative anaerobic pathogen found in soil and water, on vegetation, food contact surfaces and in raw food materials including seafood. It grows at refrigeration temperatures and up to 14% sodium chloride making it almost impossible to control in fresh or minimally-processed seafood under aerobic or anaerobic storage conditions. This thesis considers strategies to control growth of this bacterium on seafood using both established and novel non-thermal technologies and seeks to elucidate physiological mechanisms underlying one of the approaches, namely high pressure processing. Chapter 1 reviews the microbiology of seafood including normal microbiota, spoilage processes, pathogen ecology and occurrence and non-thermal processes that are currently used or have the potential to be utilized by the seafood industry. It serves as reference material for the following chapters. Chapter 2 describes an empirical assessment of several preservatives proposed as antilisterial agents. In collaboration with a local Atlantic salmon smokehouse, three commercially available antimicrobial preparations were applied directly to salmon fillets prior to smoking with the intent to stop Listeria monocyto genes growth on vacuum packed cold smoked salmon (CSS). The challenge trial extended over 40 days at 4°C and 10°C. Microbial and sensorial analyses were conducted in parallel. Results showed that two of the three treatments evaluated presented listeriostactic activity. The remaining compound appeared not to penetrate in the salmon flesh and challenge the Listeria monocyto genes introduced to the inner flesh after slicing. From the sensorial point of view one of the successful Listeria monocyto genes growth inhibitors performed slightly better than the other but significantly better than the untreated CSS, making it a good candidate to control the growth of this pathogen in this commodity. A search for novel, cold-active, anti-listerial bacteriocins is the focus of Chapter 3. Specifically, 1600 Actinobacterial isolates from Antarctic or Sub-Antartcic regions were screened against five different Listeria monocyto genes strains for their capacity to produce cold active antimicrobials. Several promising isolates were identified and their active products partially characterized. The investigation demonstrated that Antarctic or Sub-Antarctic soils harbour potentially valuable antimicrobial producers with specific capacity to target single pathogen species and their potential to food safety and industry. Future bio-prospecting research for antimicrobials against pathogens of human concern should include species from other extreme environments as well. Chapter 4 and 5 describe studies concerning physiological responses of Listeria monocyto genes to high pressure processing (HPP). Chapter 4 explores whether the cell membrane is an important mediator of the effects of HPP and reports studies of changes in the fatty acid composition of the membrane in response to HPP. The results suggested that under pressure, irrespective of the growth phase, Listeria monocyto genes tries to adapt by changing the abundance of iso branched-chain fatty acid of its cell membrane. This fatty acid adaptive response is different from that caused by cold, pH and heat stresses. In Chapter 5 microarray technology is used to assess changes in gene expression under the same experimental conditions showing that HPP seems to invoke a cell maintenance state but strongly suppresses genes associated with catabolism and virulence. Chapter 6 synthesises the results of the work undertaken, attempts to determine the applicability of the novel non-thermal technologies (applied alone or as part of a multi hurdle approach) to increase the safety of minimally processed seafood products against listeriosis and identifies future research needs.